(untitled) (Research, Society and Development, 2022)
Body image dissatisfaction (BID) has been increasingly noticeable among adolescents. The aim of this study was to identify what is portrayed by scientific articles, in recent years, about IIC in adolescents and its beauty with the media, imposed by society and eating habits. From a bibliographic review carried out through a search for articles published in journals indexed in the Portal Periódicos da Capes, from January 2015 to October 2021, with the theme of IIC (BID) in adolescents aged 12 to 19 years. We analyzed 12 articles, checked and verified application of those for inclusion. In general, there was a common message regarding cultural influence, that boys are encouraged to practice sports activities, with a greater focus on the development of physical strength, and girls are encouraged to do physical exercises to lose weight, and such conditions may be driven by a social and media standard of beauty. Well-being factors, mood disorders and depressive disorders, may be with IIC (BID). In view of these findings, it is necessary for all young people, through public policies, in the most diverse environments, such as school provision, opportunity to discuss body image, media and society in order to minimize health and social problems, as a result of the imposition of a social-media standard of beauty.